An evaluation of the source selection elements of the prototype UMLS Information Sources Map. - Masys, D. R. (American Medical Informatics Association, 1992)
The Information Sources Map (ISM) is a component of the National Library of Medicine's Unified Medical Language System (UMLS) project. The ISM is intended to provide both human-readable and machine-interpretable information about the content, scope, and access conditions for various information sources such as databases, expert systems, and the organizations which make these information sources available. Automated source selection is supported by three types of indexing in the ISM: Medical Subject Heading (MeSH) terms and subheadings; Semantic Types from the UMLS Semantic Network; and Semantic Type Relations, which depict pairs of semantic types joined by a relationship chosen from the Semantic Network. This paper reports a study of the recall and precision of the source selection elements in the prototype version of the ISM.